A Statewide Multisource Analysis of Supplemental Oxygen–Related Fires and Burn Injuries. - Klas, Karla S; Zorkot, Dayan; White, Michael; Pitogo, Alita (Journal of Burn Care & Research)
Despite the increasing prevalence of home oxygen therapy, its associated injury risks remain underrecognized. This study analyzed the statewide incidence of oxygen therapy-related fires, burns, and deaths to identify systemic barriers for data capture, outline improved surveillance pathways, and inform prevention strategies. Retrospective, multisource analysis of statewide data (2020-2023) from death certificates, hospital admissions, registries, and fire incident reports. Liaisons performed free-text field searches. Data reported in de-identified aggregate counts and analyzed descriptively for comparison. Reporting was highly inconsistent across all data systems, without specific International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) injury codes (top used: flammable material, uncontrolled fire). State National Fire Incident Reporting System data revealed a total of only 2 oxygen therapy fire deaths (mean 3.5 fires/year). In sharp contrast, death certificates and fire inspectors reported a mean 9.8-10.3 deaths/year with 97% linked to smoking, confirming home oxygen therapy deaths are underreported by a factor of 20 in state fire incident data. Four hospitals reported a mean of 17.9/year (range 13-31) oxygen therapy admissions each, with combined 4-year total of 285 (range 51-124). This represents 33% of all home oxygen therapy patients compared to published national burn center data. Home oxygen burns and deaths are underreported in state and national datasets. Most incidents are preventable, with smoking as primary ignition source. Lack of dedicated injury codes, gaps in trauma/emergency medical services variable data, and data suppression thresholds prevent reporting of low-frequency events. Establishing specific ICD-10-CM codes and cohesive prevention strategies are necessary to reduce this injury burden.